(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: The emergence of political entities, as one of the first stages of the development of the state in its contemporary form, generated the need to enter into mutual relations between these entities and each other, whether this relationship took a temporary or permanent form. Then the emergence of the state in its modern concept led to the divergence of relations between it and other countries, hence the first nucleus of the diplomatic representation system began, in the form of temporary diplomatic missions, which evolved to take the form of permanent diplomatic missions. Since its inception, the Islamic State has sought to strengthen and consolidate its mutual relations with other non-Islamic countries and groups, and diplomacy in the era of our Holy Prophet – may God’s prayers and peace be upon him – represented the ideal stage in the history of Islamic diplomacy. However, looking at what was followed during the era of the Holy Prophet, peace and blessings be upon him, we would find that it is similar to what is followed in our present time under the name of private or temporary diplomacy. There is no doubt that informing the members of the diplomatic mission of performing the duties of the diplomatic post requires that these people enjoy a set of immunities and privileges necessary to perform the tasks entrusted to them to the fullest, those immunities that our noble Messenger had emphasized many of, and he followed the guidance of the Rightly Guided Caliphs after him.